2011
DOI: 10.1007/s11273-011-9223-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term spatial and temporal variation of sediment oxygen dynamics in a tropical tidal salt flat

Abstract: Short-term spatial and temporal heterogeneity of oxygen dynamics and net primary production were studied in a tree day diurnal variation at a tidal tropical salt flat in the estuarine system of Sepetiba/Guaratiba coastal plain, Rio de Janeiro, Brazil. Oxygen concentrations were measured in situ with high temporal and spatial resolution oxygen microsensors. The results showed a remarkable heterogeneity of both oxygen penetration depth (from 0.18 to 0.85 cm) and net primary production (from -0.085 to 0.115 lmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Since the light intensity used in our microcosm study is common in field conditions (especially in the tropics) and the CO 2 concentrations are close to our actual and projected future atmospheric conditions (380 and 550 ppm, respectively), we suggest that phototrophic communities in aquatic shallow ecosystems can be carbon limited. Field studies in a tropical tidal salt flat revealed repeated flattened oxygen profiles during day time (Oliveira et al, 2011), corroborating our suggestion.…”
Section: Back Closesupporting
confidence: 89%
“…Since the light intensity used in our microcosm study is common in field conditions (especially in the tropics) and the CO 2 concentrations are close to our actual and projected future atmospheric conditions (380 and 550 ppm, respectively), we suggest that phototrophic communities in aquatic shallow ecosystems can be carbon limited. Field studies in a tropical tidal salt flat revealed repeated flattened oxygen profiles during day time (Oliveira et al, 2011), corroborating our suggestion.…”
Section: Back Closesupporting
confidence: 89%